An investigation into blood microbiota and its potential association with Bacterial Chondronecrosis with Osteomyelitis (BCO) in Broilers - Mandal, Rabindra K. (Sci Rep, 2016)
Bacterial chondronecrosis with osteomyelitis (BCO) is a common cause of lameness in commercial broiler chickens worldwide. BCO represents substantial production loss and welfare issues of chickens. The bacterial species or communities underlying BCO pathogenesis still remain to be fully characterized. To gain insights on blood microbiota in broilers and its potential association with BCO, blood samples collected from healthy (n = 240) and lame (n = 12) chickens were analyzed by deep sequencing of 16S RNA genes. The chicken blood microbiota were dominated by Proteobacteria (60.58% ± 0.65) followed by Bactroidetes (13.99% ± 0.29), Firmicutes (11.45% ± 0.51), Actinobacteria (10.21% ± 0.37) and Cyanobacteria (1.96% ± 0.21) that constituted 98.18% (± 0.22) of the whole phyla. The bacterial communities consist of 30–40 OTUs in the blood of broiler chickens, regardless of ages and other environmental or host conditions, and the blood microbiomes of BCO chickens were largely distinct from those of healthy chickens. In addition, Linear discriminant analysis (LDA) effect size (LEfSe) method revealed that Staphylococcus, Granulicatella, and Microbacterium were significantly enriched in BCO chickens as compared to healthy chickens. The results from this study have significant implications in understanding blood microbiota present in broiler chickens and its potential role in BCO pathogenesis.